That Special Little Baby - Peddicord, Jane Ann; So, Meilo (Orlando : Harcourt, 2007)
A rhyming exploration of the slowly expanding world of the newborn baby.
Keywords: Infants -- Fiction; Children -- Fiction; Stories in rhyme